Representation of Writing Skill Importance In a Video Advertisement From The Perspective of Multimodal Discourse Analysis - Natasha Puspa Dewi; Tatan Tawami (Peneliti.net, 2022)
The purpose of this study is to analyze the verbal and visual modes that are presented in a video advertisement. This study also aims at finding the relation of these two modes in representing a writing skill's importance in a video advertisement. The method that is used in this study is a descriptive qualitative method that used a Multimodal Discourse Analysis (MDA) as an approach. The theory of multimodality by Kress and Van Leeuwen as well as the theory of systemic functional grammar by Halliday and Matthiessen were applied to analyze the data. The data was collected using observation of a video advertisement; the study case is Grammarly’s YouTube advertisement entitled “Save Time Editing Papers | Grammarly Makes One Click Simpler”. The results show that the combination of verbal and visual modes could represent the writing skills importance thoroughly in the video advertisement. It was discovered that the importance of writing skills was clearly depicted in the video advertisement through the analysis of visual modes using representational, interactive, and compositional meaning. This finding is also supported by the analysis of verbal modes using the systemic functional grammar theory, which supports the meaning created in visual mode. Therefore, it can be concluded that the visual and verbal modes can show the representation of writing skills’ importance in a video advertisement clearly. This study is expected to be a reference for further research that is related to this topic.